The Pell sequence in the tricomplex ring - Costa, Eudes Antonio; Monteiro, Francival Santos; Souza, Vitor Manoel Alves de; Santos, Douglas Catulio dos (C.Q.D. - Revista Eletrônica Paulista de Matemática, 2025)
In this study we investigate a Pell-type sequence, perpetrated by a second-order linear recurrence which specifies the Horadam sequence. Here, we present, study and analyze results concerning this new class of Pell sequences.